Studi Pengembangan Potensi Kawasan Wisata Kabupaten Kerinci - Rahayu, Silvia; Yadewani, Dorris (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to determine the internal and external factors for developing the Kerinci Lake tourist attraction and to determine the strategy for developing the Kerinci Lake tourist attraction. The data used is primary data obtained from respondents. The analytical tool used in this research is SWOT analysis. Based on the study carried out, it was concluded that the strategy for developing the Kerinci Lake tourist attraction is in quadrant 1, namely the Rapid Growth Strategy. By using the SO strategy, the strategy for developing the Kerinci Lake tourist attraction is to maintain the existence of natural resources which have great potential as tourist attractions, establishing cooperation with other parties in developing facilities and infrastructure as well as tourist attractions. Apart from that, the strategy that needs to be carried out is to develop the Lake Kerinci tourist attraction with the aim of providing comfort and security by involving the participation of the community of the tourist attraction area and its unique socio-cultural (community traditions) to increase Opportunities in the current natural tourism trend in order to drive the community's economy and improve PAD.